THE USE OF REMOTE SENSING IN ENVIRONMENTAL MATERIAL MONITORING THE AREAS OF MINING URANIUM - Зацерковний, В. І.; Тішаєв, І. В.; Комарова, У. Ю.; Шишенко, О. І. (Science-based technologies, 2016)
In the article the approach to use Earth Remote Sensing materials for monitoring and forecasting of uranium development is examined. Energy crisis in Ukraine is aroused by deficit of organic fuel which is used to produce energy. One of the way to overcome energy crisis is to use nuclear power engineering and particularly uranium. Uranium fields in Ukraine have a number of peculiarities which provide competitiveness of manufactured uranium concentrate: huge stocks of uranium fields allow to use highly-productive production systems; big hardness of carrying rocks allow to make production without anchors and to make huge volumes of stopes; small water flowing to excavations; relatively simple tools of protection against radiation through small content of uranium in minerals. However serious obstacle for further development of atomic energy industry are problems of environmental pollution. The Methodological approaches to use Earth Remote Sensing technologies are examined, as well as modern ways of their analysis to detect, evaluate and monitor the processes which take place in landscapes as a result of exploitation of uranium mining mines. For evaluation of conditions of surrounding territories the processing of multispectral satellite data was done: elimination of atmospheric effect, putting images to unified scale and further transformation. The algorithm for introduction of monitoring of uranium fields was offered, it was offered with usage of technologies of ERS and GIS based on methods of geo-information mapping and intended for creation of maps of ecological condition of landscapes. Multi-year changes of project coverage of plant formation were calculated, as well as level of lands erosion which are remote indicators of lands condition